La gestión administrativa y su incidencia en la inclusión educativa para el desarrollo institucional de la Unidad Educativa Centro Educativo Cotopaxi “CEC”. Estrategias inclusivas. - Pilozo Agua, Fátima (2016)
Education is an issue of vital importance that transcends the time, especially in regards to the inclusion that is why that is born the theme: the administrative management and its impact on educational inclusion of Educational Unit “CEC”, in the city of Latacunga, Cotopaxi province, academic year 2016 - 2017; this had as objective to strengthen the administrative management through the inclusion for the institutional development. In the study methods were applied as the field, which helped me to observe the real situation on of educative inclusion that about students with special educational capacities, in the same way methods were applied as the analytical and the synthetic with which they could be applied to different surveys and interviews to the educational community formed by the authorities, teachers, parents and students. By means of the results obtained it was revealed that within this inclusion requires that the teacher integrates first to the classroom as infants are often integrated alone. It should also be emphasized that one of the greatest drawbacks are the teachers, since they are overwhelmed by fear, damages and not knowing how to react to any situation they face. Through this was defined a guide on the teaching and learning process, in which the teacher will focus its attention and take advantage of the various forms of access to learning: emotion, sensation, feelings, intuition and reason, in which the inclusion in the educational center must be in conditions to include all child, taking into account that the diversity is the essential condition of human beings.